172k views
4 votes
For the Dividend Growth Model, the equation can be written as follows: P0 = =D1/(RE – g). How can this equation be rearranged?

1 Answer

5 votes

Answer:

Re = (D1 ÷ P0) + g

Step-by-step explanation:

The rearrangement of the equation is as follows:

Given equation is:

P0 = D1 ÷ (Re - g)

where,

P0 = Price of the stock

D1 = Dividend at year 1

Re = Required rate of return

g = Growth rate

It can be rearrange as

Re - g = (D1 ÷ P0)

Or

Re = (D1 ÷ P0) + g

The Re = (D1 ÷ P0) + g is the correct answer and the same is to be considered

User Dimiter
by
6.0k points